Transformation of Make A Match Learning Model in Primary School Indonesian Language Learning: A Systematic Literature Review - Mariatul (Universitas Pendidikan Ganesha, 2025)
Indonesian language learning in elementary schools still faces various challenges, including low student learning interest, limited active engagement during lessons, and the lack of diverse instructional models used by teachers. These conditions result in suboptimal learning outcomes and underdeveloped literacy skills among students. This study aims to analyze the effectiveness of the Make a Match learning model in improving learning outcomes and literacy skills in elementary school students. The research employed a Systematic Literature Review (SLR) design through stages of identification, selection, analysis, and synthesis of relevant studies. Data were collected through a literature search on Google Scholar with publication criteria from 2020 to 2025. From 292 identified articles, eight met the inclusion criteria for further analysis. Data were analyzed descriptively and qualitatively by examining empirical findings from each study. The results reveal that the Make a Match model is effective in enhancing learning outcomes, motivation, student engagement, and literacy skills, particularly reading and writing. Moreover, this model is flexible for application across different grade levels and learning topics and can be integrated with other teaching strategies to foster collaborative and interactive learning environments. The study concludes that the integration of the Make a Match model serves as an innovative alternative to improve the quality of Indonesian language learning processes and outcomes in elementary education.